TikTok and Grammar Skills in English: Perspectives of English Major Students - Revesencio, Nicole I.; Alonsagay, Rodemie R.; Dominguez, Luzlyn I.; Hormillosa, Donna Mae I.; Ibea, Clint Hector I.; Montaño, Mesty Mae S.; Biray, Ersyl T. (Future Science / FSH-PH Publications, 2022)
This descriptive quantitative study aimed at establishing the advantages and disadvantages of watching TikTok to the English grammar skills development of college education students specializing in English enrolled at a state university in Western Visayas during the second term of the academic year 2021-2022. Field experts validated the researcher-structured questionnaire transformed into the Google form was utilized to gather data online considering the government-imposed restrictions related to the pandemic at the time of instrument administration. Findings revealed that the majority of the respondents are 20-year-old, females, and had an average final grade of between 1.75–1.99 in all the English subjects during the last semester of the preceding academic year. A number of them spend 30 minutes to an hour watching TikTok videos that have English grammar-related content in a day. The majority of them had 3 days per week watching TikTok videos with English grammar-related content. Almost all of them revealed that watching TikTok aids them in discovering and comprehending new words in English. However, there were instances that the TikTok videos instead confuse their grammar use. This implies that watching the TikTok application has a more positive impact on the grammar skills in English of college students than its negligible flaws in the process.